Treatment of cirrhotic tense ascites with Dextran-40 versus albumin associated with large volume paracentesis: a randomized controlled trial - García Compeán, Diego; Blanc, Pierre; Larrey, Dominique; Daures, Jean-Pierre; Hirtz, Jacques; Mendoza, Eduardo; Maldonado, Héctor; Michel, Henri (2002)
Intravenous albumin infusion prevents complications after large-volume paracentesis (LVP), particularly paracentesis-induced circulatory dysfunction (PCD), and improves patient survival. However, albumin is expensive. We compared a low-molecular weight dextran (Dextran-40) with albumin in treating LVP in cirrhotic patients with tense ascites. Sixty-nine cirrhotic patients were included and 96 LVPs were performed. Any repeat punctures on the same patient were at least three months apart. Patients were randomized to receive either i.v. Dextran-40 infusion (Group I, n = 48) or i.v. albumin infusion after LVP (Group II, n = 48). Clinical, biochemical, and hormonal evaluations were done before and after LVP. Patients were followed up for the detection of any recurrence of ascites or complications.The two groups were similar in age, sex, and etiology of cirrhosis, and in the volumes of ascites recovered. Significant decreases in mean arterial pressure were observed in both groups 24 and 48 h after LVP. Urine volumes increased significantly at 24 h in both groups (p 0.05). Ascites recurrence rates and survival were similar in the two groups. In conclusion, Dextran-40 was thus not as efficacious as albumin for preventing PCD.